Development of material selection expert system for polymer-based composite materials - Abd Manab, Mohd Fairuz (2011)
The main objective of this research was to determine the most optimum polymer based composite material for engineering applications. Three engineering application involved in the material selection of polymer based composite are small boat for marine application, thyristor for electronic application and interior car panel for automotive application. The objective was achieved by proposing material selection framework and implementing expert system approach using IF/THEN logic rules. Various attributes and criteria such as tensile strength, tensile modulus, flexural strength, flexural modulus, impact strength, density, and water absorption of polymer based composite were considered. To determine the most suitable material for polymer based composite for engineering application, expert system shell Exsys Corvid software was used. The research covered the development of user interface for easy customization, material database using MetaBlock system, rule-based system, and constraint satisfaction and constraint violation. The research revealed that 63% glass fibre reinforced vinyl ester composite is the most suitable for small boat and 40% glass fibre polycarbonate composite for thyristor body casing and 30% glass fibre polyphenylene ether composite for interior car panel. The sensitivity analysis is performed by adjusting the range of design requirements in order to verify the developed material selection system sensitivity. Overall, it can be concluded that the proposed material selection approach allows designer to determine the most suitable materials for polymer based composite engineering application.